Survival rate of dental implant placed using various maxillary sinus floor elevation techniques: A systematic review and meta-analysis - Darshana Shah; Chirag Chauhan; Rajal Shah (Wolters Kluwer Medknow Publications, 2022)
Aim: The aim of this systematic review is to evaluate the survival rate of dental implant placed using different maxillary sinus floor elevation techniques. Setting and Design: PRISMA guidelines were used for this systematic review and meta-analysis. Materials and Methods: Relevant articles were searched from Medline, PubMed, Google Scholar, ScienceDirect, and Cochrane trials. Articles published in English language were selected. Hand search was further conducted. For risk of bias, two tools were used, i.e., Cochrane tool for randomized controlled trials (RCTs) and new castle Ottawa quality assessment tool for non-RCTs. Statistical Analysis: For statistical meta-analysis RevMan 5.4 software was used. Results: Seventeen studies were finalized. All studies were included in the meta-analysis to check the implant survival rate. There is no statistical difference between direct and indirect techniques, and forest plot was derived for direct approach (P = 0.688, 95% confidence interval [CI] 0.9691) and for indirect approach (P = 0.686 and 95% CI 0.970). Conclusion: There is no statistically significant difference in the survival rate of implant placed using direct or indirect sinus lift approach procedures. Hence, the technique is selected as per the indications given for each direct and indirect procedure.